Limit state design of a single-span PSC box Girder Bridge for a seismically active Hilly River crossing: Case study of the Mardi River, Nepal - Shakya, Alin Chandra; Adhikari, Samaya; Paudel, Sunil; Katuwal, Roshan; Niroula, Sibin; Khanal, Satendra (Journal of Innovations in Engineering Education, 2025)
This study presents the complete analysis and limit state design of a 40-meter single-span box girder bridge made of prestressed concrete (PSC) that spans the Mardi River in Kaski, Nepal. In addition to regional-specific issues like seismicity and mixed traffic loading, the design takes into account a thorough site evaluation that includes in-depth topographic, hydrological, and geotechnical surveys. The effective width approach is used to analyze the deck slab, design the superstructure, a PSC box girder, for dead, live (Indian Road Congress (IRC) Class A and Class 70R traffic loads), and seismic loads. Pot Polytetrafluoroethylene (PTFE) bearings are used to transfer load from the superstructure to the substructure. Cantilever abutments and footings are substructure elements developed for stability and load transfer efficiency, with a focus on scour and seismic resistance. A strong, affordable, and long-lasting infrastructure solution appropriate for challenging topography is demonstrated by the provided design, which closely complies with IRC norms.